Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 1 - Functions - 1.1 Review of Functions - 1.1 Exercises: 58



Work Step by Step

$f(x) = 4x-3$ $\frac{f(x+h)-f(x)}{h}=\frac{((4(x+h)-3)-(4x-3)}{h}=\frac{4x+4h-3-4x+3}{h} =\frac{4h}{h} =4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.